Facilities along the Syrian Hajj Route in Southern Jordan with Special Reference to the Fort of Fassou'ah and Its Water System - Shqairat, Mansour (Richtmann Publishing, 2020)
The Syrian Hajj (Pilgrimage) Road, which links Damascus with the holy cities of Medina and Mecca in Saudi Arabia, was a historical road supplying the most basic needs of the pilgrims during this long journey. Most important are the water control and storage systems facilities which are reflected as archaeological remains. This paper discusses the water supply installations associated with the Hajj route with special reference to the Ottoman fort of Fassou’ah as one of the Hajj stations in southern Jordan.